Adrienne Asch: Memories of a Close Friend and Collaborator - Wasserman, David (The Hastings Center report, 2014)
Adrienne Asch inspired, challenged, and provoked a generation of bioethicists and philosophers who were discovering the subject of disability. For Adrienne, disability was a complex phenomenon that raised universal issues of embodiment, justice, well-being, and identity. She insisted that bioethicists and philosophers who invoked disability in discussions about these issues first learn something about it, for which her own work provided critical insights. She argued eloquently that those who relied on unsupported assumptions about disability, even in the most arcane debates, reinforced harmful stereotypes and impoverished their own thinking. At the same time, she urged that the claims of disability scholars concerning discrimination, fairness, and kindred issues be made with philosophical clarity. She was fearless with the smug and insular in both fields, but generous with those, like me, who were merely naive.